Peran E-Commerce Dalam Pemberdayaan Umkm Di Indonesia - Sri Hartono; Nurjannah; Mahadi; Syahroni; Faisal Asmen (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This research examines the role of e-commerce in empowering Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a qualitative approach based on literature review. Analysis of scientific literature from 2021-2025 identifies three main focuses: mechanisms of e-commerce in enhancing MSMEs capacity and competitiveness, determinant factors of digital technology adoption effectiveness, and strategies for sustainable empowerment optimization. Research findings indicate that electronic commerce platforms function as catalysts for market access expansion, digital literacy improvement, and business turnover growth acceleration. Adoption effectiveness is influenced by business operators' digital literacy, technology infrastructure availability, capital access, and socio-cultural ecosystem support. Optimization strategies require multi-stakeholder collaboration through intensive training programs, pro-MSME policies, and inclusive infrastructure development. This research contributes to enriching digital economy literature with Indonesian contextual perspectives and provides policy recommendations for strengthening MSMEs digital transformation as national economic pillars. Practical implications include the necessity of continuous mentoring and government-private sector synergy in creating conducive digital ecosystems for micro-enterprises sustainability in Indonesia.   Keywords: E-commerce, Empowerment, MSMEs   Abstrak Penelitian ini mengkaji peran e-commerce dalam pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia melalui pendekatan kualitatif berbasis kajian kepustakaan. Analisis literatur ilmiah periode 2021-2025 mengidentifikasi tiga fokus utama: mekanisme e-commerce dalam meningkatkan kapasitas dan daya saing UMKM, faktor-faktor determinan efektivitas adopsi teknologi digital, dan strategi optimalisasi pemberdayaan berkelanjutan. Hasil penelitian menunjukkan bahwa platform perdagangan elektronik berfungsi sebagai katalisator perluasan akses pasar, peningkatan literasi digital, dan akselerasi pertumbuhan omzet usaha. Efektivitas adopsi dipengaruhi oleh literasi digital pelaku usaha, ketersediaan infrastruktur teknologi, akses permodalan, serta dukungan ekosistem sosial-budaya. Strategi optimalisasi memerlukan kolaborasi multipihak melalui program pelatihan intensif, kebijakan pro-UMKM, dan pengembangan infrastruktur inklusif. Penelitian ini berkontribusi dalam memperkaya literatur ekonomi digital dengan perspektif kontekstual Indonesia dan memberikan rekomendasi kebijakan untuk penguatan transformasi digital UMKM sebagai pilar perekonomian nasional. Implikasi praktis mencakup perlunya pendampingan berkelanjutan dan sinergi pemerintah-swasta dalam menciptakan ekosistem digital yang kondusif bagi keberlanjutan usaha mikro di Indonesia.   Kata Kunci: E-Commerce, Pemberdayaan, UMKM